Biological and Molecular Characterization of Pleurotus SP: Genetic and Morphological Characterization of Pleurotus Mushroom Species (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Mushrooms have restorative just as nutritive worth and broadly utilized as human food from the time interminable. To decide the hereditary variety among Pleurotus types of mushroom utilizing morphological and arbitrary enhanced polymorphic DNA (RAPD) markers, around seven distinct species were gathered. Five species, naming Pleurotus platypus (P-6), Pleurotus flabelatus (P-7), Pleurotus florida (P-17), Pleurotus ostreatus (P-19) and Pleurotus sajor-caju (P-56) were from Canada and two Pleurotus warm-stram (P-9) and Pleurotus eryngii (P-16) from Philpines. Seven diverse morphological attributes that is, mycelial development (mm), cap measurement (cm), complete yield (kg), dampness substance (), debris substance (), nitrogen substance () and protein content () were recorded. The dendrogram dependent on morphological information isolated seven species in bunch 'A' and 'B' having four and three species, individually. The dendrogram dependent on RAPD examination created 3 groups 'A', 'B' and 'C'. Out of 14 irregular preliminaries, the greatest polymorphism was seen by groundworks OPL3 (72.70 ) and OPL11 (70).